Effect of porosity on surface of drawndown in an unsteady state drainage in porous material. I (2007)
"This work considered the unsteady state drainage of fluid from a vertical column of porous material of varying porosities in an attempt to verify variation of drawndawn surface with porosity and time using riverbed sand. Kerosene was used as the flowing fluid. Mathematical assumptions ware made in connection with Darcy's law. The result showed that the experiment which was designed from the theoretical framework agreed with the theory to a large extent, However, this is not in perfect agreement with an earlier experiment which was performed using well rounded beads in which glycerine was used as the flowing fluid. A FORTRAN program was written to study the variation theoretically and this was compared with the experimental result. There exists, a degree of discrepancy between theory and experiment indicating that, the mathematical formulations did not perfectly agree with the complex earth system as compared with the bead model that was initially used. There is a need for the modification of the mathematical formulations; nonetheless, an unsteady drawndown, pattern was attained with different porosity even in medium with very complex geometry. "